Analisis Kesulitan Belajar Siswa dalam Menyelesaikan Soal Jurnal Penyesuaian pada Mata Pelajaran Ekonomi - Melinda, Teni (Jurnal Inovasi dan Teknologi Pendidikan, 2022)
The purpose of this study was to describe the level of student learning difficulties in solving adjusting journal questions. The research was conducted at SMAN 2 Singaparna with a sample of 32 students of class XII IPS 2. The research method used was a qualitative method with descriptive research. This study describes the difficulties of students in solving adjusting journal questions. The results of the questionnaire analysis of the factors that cause student learning difficulties in solving adjustment journal questions at SMAN 2 Singaparna. It is known that the overall average of the internal factors of students' learning difficulties in completing the adjusting journal questions is 52, 05% while the overall average of the external factors of students' learning difficulties is 50, 28%. Based on the questionnaire on the internal factors of students' learning difficulties, it is known that learning difficulties are caused by a lack of basic knowledge and skills on the material studied in the form of understanding and skills in analyzing and recording transaction data; lack of interest in student learning on adjusting journal material; teachers' teaching methods are less attractive during accounting lessons and the lack of complete learning infrastructure such as an inadequate supply of accounting textbooks